Diffusion Tensor Imaging Colour Mapping Threshold for Identification of Ventilation-Induced Brain Injury after Intrauterine Inflammation in Preterm Lambs - Alahmari, Dhafer M.; Skiöld, Beatrice; Barton, Samantha K.; Nitsos, Ilias; McDonald, Courtney; Miller, Suzanne L.; Zahra, Valerie; Galinsky, Robert; Wu, Qizhu; Farrell, Michael John; Moss, Timothy J.; Hooper, Stuart B.; et al. (Frontiers in Pediatrics, 2017)
Purpose: To examine whether advanced magnetic resonance imaging (MRI) techniques can detect early brain injury caused by intrauterine inflammation and inappropriate initial respiratory support in preterm lambs. Hypothesis: Neuropathology caused by intrauterine inflammation is exacerbated by mechanical ventilation at birth, and is detectable with advanced MRI techniques. Methods: Pregnant ewes received intra-amniotic lipopolysaccharide (LPS) 7 days prior to delivery at ~125 days’ gestation (85% of gestation), whereupon lambs were delivered and randomised to receive an injurious (LPS+INJ, n=6) or protective (LPS+PROT, n=6) ventilation strategy. MRI of the brain was conducted 90 minutes after preterm delivery, using structural, diffusion tensor imaging (DTI) and magnetic resonance spectroscopy (MRS) techniques. A colour map threshold technique was utilised to compare distributions of low diffusivity voxels in the brains of LPS-exposed lambs with those not exposed to LPS (PROT, n=7 PROT and INJ, n=10). Results: No overt cerebral injury was identified on structural MRI images of any lamb. However, on DTI, axial diffusivity, radial diffusivity and mean diffusivity values were lower, and significantly more heterogeneous, in specific brain regions of lambs in the LPS+INJ group compared to the LPS+PROT group. Colour mapping revealed lower diffusivity in the thalamus, periventricular white matter, internal capsule and frontal white matter in the LPS+INJ group compared to LPS+PROT group. The MRS peak area ratios of lactate, relative to those for the metabolites creatine, choline and N-acetylaspartate, were not different between LPS exposed groups. Lambs exposed to LPS had lower diffusivity within the white matter regions assessed than non-LPS treated control lambs. Conclusion: DTI colour map threshold techniques detected early brain injury in preterm lambs exposed to intrauterine inflammation and detected differences between injurious and protective ventilation strategies. DTI mapping approaches are potentially useful for early detection of subtle brain injury in premature infants.